Análise faciológica da formação Codó (Aptiano superior) na Região de Codó (MA), leste da Bacia do Grajaú - PAZ, Jackson Douglas Silva da (Universidade Federal do Pará, 2019)
The Codó Formation, focused in this paper, is exposed in the adjacencies of Codó town, eastern Maranhão State, where it consists of intergraded shales, limestones and evaporites, laterally continuous, forming shoaling-upward successions averaging 2.5 m in thickness. Sedimentological features, the abundance of freshwater ostracodes and Charophyte algae, as well as the absence of any marine fauna, characterize this unit as a dominantly lacustrine unit, which can be described by three broad facies associations, attributed to: 1. central lake; 2. transitional lake; and 3, marginal lake. The central lake facies association represents the base of the shoaling upward successions and consists of two facies: a) black shale; and b) evaporite. The dominance of shale beds in this association indicates sedimentation in low energy depositional settings, typical of central lake areas, where the abundance of pyrite and the bituminous composition point to highly reducing conditions. The scarcity of infauna is indicated by the complete absence of bioturbation, which is consistent with anoxia. The evaporite facies point to a highly saline lake setting. The transitional facies association consists of: a)laminated argillite; hb)lime- mudstone; c)peloidal limestone (mudstone to packstone); and d)meso-crystalline limestone. These deposits, between central lake and marginal lake facies associations, own in the middle portion of the shoaling upward cycles, consistent with a transitional lacustrine setting. The marginal lake facies association represents the top of the shoaling upward successions and consists of a variety of intergrading lithofacies: ajmassive pelite; b)calcite-arenite; Cc) ostracodal limestone (wackestone to grainstone); d) pisoidal limestone (packstone) ; e)gipsite-arenite; £f) tuffa; and 9) rhythmite. These deposits show an abundance of sedimentary features (i.e., paleosoil, karstic surface, fenestrae) typical of subaerial and/or meteoric exposure, which is consistent with their interpretation as marginal lake deposits. A lacustrine facies model with ramp margin and low energy flow is proposed for the study area, taking into account the following characteristics: 1) low rates of sediment supply; 2) presence of areas with low relief around the lacustrine basin; 3) abundance of sedimentary features recording episodes of subaerial and/or meteoric exposure; and 4) prevalence of marginal facies. This interpretation is further suggested by: 1) the small thickness of the depositional cycles, which is attributed to decreased accommodation; 2) absence of turbiditic deposits, which are typical in lacustrine settings with pronounced slope break; and 3) absence of resedimented deposits, which are also common in bench margin lacustrine settings. The abundance of black shales and evaporites suggests a hydrologically closed lacustrine basin with stratified and saline water column for the study area. The depositonal cycles identified reveal a regressive character for this lacustrine succession. Three types of cycles were recognized: 1) complete shoaling-upward cycle; 2) incomplete shoaling-upward cycle; and 3) flooding-upward cycle. The origin of these cycles is attributed to tectonism, based on the assymetrical vertical stacking pattern. This interpretation is corroborated by the presence of sin- sedimentary deformational features related to sin- depositional sismic activity. The faciological, palaeontological and geochemical data presented in this work suggested on show that the Late Aptian marine transgression recorded in the northern portion of the São Luís-Grajaú Basin did not reach the Codó area.